ADSORPSI METILEN BIRU DENGAN MENGGUNAKAN ARANG AKTIF DARI DAUN TANAMAN DOYO (Curculigo latifolia) - Pasa, Jessica Indriyani; -, Aldiansyag; Septiani, Risky; Prastika, Nanda Diah; Markus, Rio Mardani; Lestari, Sri; -, Sukemi; Gunawan, Rony (Jurusan Kimia FMIPA UNMUL, 2024)
Methylene blue adsorption research has been carried out using activated charcoal from Curculigo latifolia. This research aims to determine the characteristics of the Curculigo latifolia activated charcoal made and the optimum conditions for the adsorption of methylene blue by Curculigo latifolia activated charcoal. Physically activated charcoal is made from Curculigo latifolia which is carbonized at 400°C for 30 minutes, then the physically activated charcoal is soaked in 0.5 M H2SO4 solution for 24 hours to produce chemically activated charcoal. The results showed that the optimum pH for methylene blue adsorption obtained from the Curculigo latifolia activated charcoal adsorbent was physically activated at pH 7 and chemically activated at pH 9. The optimum contact time obtained from the physically and chemically activated Curculigo latifolia activated charcoal adsorbent occurred at a contact time of 15 minutes and 30 minutes. Adsorption of methylene blue by chemically activated Curculigo latifolia activated charcoal follows the Langmuir adsorption isotherm while physically activated charcoal follows the Freundlich adsorption isotherm. The optimum adsorbent mass of physically and chemically activated charcoal is 0.2 g and 0.25 g.